2015
DOI: 10.1016/j.rehab.2014.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Stroke management: Informal caregivers’ burdens and strians of caring for stroke survivors

Abstract: Caring for stroke survivors put social, emotional, health and financial burdens and strains on the informal caregivers. These burdens and strains increase with duration of stroke, intimacy, smaller number of caregivers and length of daily caregiving. Therefore, informal caregivers should be involved in the rehabilitation plan for stroke patients and their well-being should also be given adequate attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
91
1
22

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(119 citation statements)
references
References 20 publications
5
91
1
22
Order By: Relevance
“…Most research on family care had reported that the caregivers bear the greater burden [14,15]. Many of these researches on caregiver burden were concentrated on caregivers of chronically ill patients such as those with dementia, Alzheimer's disease and heart disease [9,[16][17][18][19]. There seems to be less focus on the wider caregiver roles, especially regarding caregivers of recipients who are not necessarily physically or mentally ill. Also, there is a paucity of research exploring the reactions to care for the elderly person, especially regarding the frail, older members in the household.…”
Section: Introductionmentioning
confidence: 99%
“…Most research on family care had reported that the caregivers bear the greater burden [14,15]. Many of these researches on caregiver burden were concentrated on caregivers of chronically ill patients such as those with dementia, Alzheimer's disease and heart disease [9,[16][17][18][19]. There seems to be less focus on the wider caregiver roles, especially regarding caregivers of recipients who are not necessarily physically or mentally ill. Also, there is a paucity of research exploring the reactions to care for the elderly person, especially regarding the frail, older members in the household.…”
Section: Introductionmentioning
confidence: 99%
“…Salah satu fokus dari psikoedukasi adalah mengembangkan keterampilan penyelesaian masalah dan mengembangkan keterampilan crisis intervention dan dengan ditingkatkannya kemampuan caregiver dalam merawat penderita stroke maka dapat menghadapi situasi permasalahannya sehingga masalah yang dirasakan dapat berkurang dan dapat membantu caregiver menghadapi stressor karena klien sakit (Gbiri, Olawale and Isaac, 2015) Menururt peneliti terapi psikoedukasi keluarga yang diberikan mampu menurunkan beban keluarga yang pada akhirnya dapat meminimalkan dampak yang dirasakan dalam merawat penderita stroke, sehingga keluarga mampu merawat penderita stroke dengan baik. faktor lain seperti agama, budaya, harapan dan pengabdian juga mempengaruhi beban yang dirasakan oleh caregiver, oleh sebab itu pada kelompok kontrol juga dapat terjadi penurunan beban Dalam penelitian Gonzales et al(2010) (Jeong, Myong and Koo, 2015).…”
Section: Hasil Dan Pembahasanunclassified
“…В изучаемых регионах уве-личилось выявление основных факторов риска инсульта, таких как артериальная гипертензия, сахарный диабет и дислипопротеинемия. Про- спективные исследования эпидемиологии ин-сульта, проводимые в экономически развитых странах мира, подтверждают отсроченный эф-фект мероприятий по первичной профилактике инсульта [6]. Первичная профилактика требует масштабной работы и на уровне организации здравоохранения, и на популяционном уровне, включающем повышение медицинской грамот-ности населения.…”
Section: материал и методыunclassified
“…Максимальные потери DALY (disability-adjusted life years) составили при инсульте 47,3 % сре-ди всех неврологических заболеваний, второе и третье места по индексу DALY приходились на мигрень (13,1 %) и менингит (10,1 %). Инсульт привел к 67,3 % летальных исходов среди невро-логических заболеваний в возрастной группе до 75 лет, на втором месте была болезнь Альцгейме-ра и другие формы слабоумия (20,3 %), далее сле-довали менингиты, составив 4,0 % летальных ис-ходов [6,8,10,11]. По результатам исследования, с 1990 по 2015 г. эпидемиологические показатели инсульта вначале увеличивались, затем уменьша-лись, в целом произошло снижение смертности от инсульта на 30 %.…”
unclassified